2-D honeycomb MI wave communication system - Feng LIU; Zhi-jun ZHANG; Xiao-tong ZHANG; Jin-wu XU (Tongxin xuebao)
To realize the high reliable communication and the wireless power transmission in the wireless underground sensor network,a new type of 2D honeycomb magneto-inductivenetwork was put forward at VLF band.The system model was established,and bandwidth,group velocity and beam forming technologies were researched based on the cur-rent dispersion equations.Simulation with Runge-Kutta method was carried out to verify the efficiency of the network.The result show that the omnidirectional propagation can be realized in the proposed honeycomb network with more bal-anced bandwidth and group velocity in every direction compared with the square lattice structure.Directional communi-cation can also be realized based on the cooperative multi-antenna technology.The proposed honeycomb mag-neto-inductive network is very suitable to build wireless sensor networks with high connectivity and power efficiency in the underground environments.